PENINGKATAN HASIL BELAJAR MATEMATIKA FPB DAN KPK MELALUI MEDIA DAKON MATEMATIKA KELAS IV SDN BOGOREJO KECAMATAN BANCAR KABUPATEN TUBAN - Hikmah, Kholishotul; Fadiana, Mu'jizatin (Jurnal Pendidikan Dasar, 2023)
Maths is one of the subjects that plays an important role in education. So far, learning mathematics at the primary school level has mostly been carried out using the lecture method, teachers are reluctant to use learning media, arguing that the use of learning media requires large costs and is not practical. The problem that occurs at SDN Bogorejo, Bancar Subdistrict, Tuban Regency is the low mathematics learning outcomes of students on the material of Greatest Common Factor (FPB) and Least Common Multiple (KPK). This is evident from the implementation of daily tests, the results obtained have not reached the KKM (Minimum Graduation Criteria) determined by the school which is 75. This Classroom Action Research uses the "Dakon Matematika" media. The "Dakon Matematika" media is an effort to overcome the problem of low scores of students in learning mathematics, especially the material of FPB and KPK. The results showed that students' mastery of the learning material showed an increase. This can be shown by the results of the learning evaluation increasing from Cycle I 70.37% and Cycle II 92.59% after using the Dakon Matematika media. The increase in learning outcomes in the form of average scores has increased from Cycle I 71.48% and Cycle II 89.63%. The observation results showed that there was an increase in student activity which initially in Cycle I was only 62.96% to 96.30% in the second cycle.